Human tissue inhibitor of metalloproteinases‐1 improved wound healing in diabetes through its anti‐apoptotic effect - Lao, Guojuan; Ren, Meng; Wang, Xiaoyi; Zhang, Jinglu; Huang, Yanrui; Liu, Dan; Luo, Hengcong; Yang, Chuan; Yan, Li (Experimental dermatology, 2019)
Impaired wound healing accompanies severe cell apoptosis in diabetic patients. Tissue inhibitor of metalloproteinases‐1 (TIMP‐1) was known to have effects on promoting growth and anti‐apoptosis for cells. We aimed to determine the actual levels of TIMP‐1 and cell apoptosis in: (i) the biopsies of diabetic and non‐diabetic foot tissue and (ii) the human fibroblasts with or without treatments of advanced glycation end‐products (AGEs). Next, we aimed to determine the improved levels of cell apoptosis and wound healing after the treatments of either active protein of TIMP‐1 or in vivo expression of gene therapy vector‐mediated TIMP‐1 in both the human fibroblasts and the animal model of diabetic rats. The levels of TIMP‐1 were significantly reduced in diabetic skin tissues and in AGEs‐treated fibroblasts. Both AGEs‐treated cells were effectively protected from apoptosis by active protein of TIMP‐1 at appropriate dose level. So did the induced in vivo TIMP‐1 expression after gene delivery. Similar effects were also found on the significant improvement of impaired wound healing in diabetic rats. We concluded that TIMP‐1 improved wound healing through its anti‐apoptotic effect. Treatments with either active protein TIMP‐1 or TIMP‐1 gene therapy delivered in local wound sites may be used as a strategy for accelerating diabetic wound healing.